Modeling student efficacy in Massive Open Online Courses (MOOCs) and meaningful learning - Norliza Ghazali
This research explored two important constructs in 21st century e-education—students' MOOC-efficacy and meaningful learning--among undergraduate students in selected public universities in Malaysia. Its main objectives were to verify and construct validate the psychometric properties of two measurement models (i.e. students' MOOC-efficacy and meaningful learning), and examine the association between students' MOOC-efficacy and meaningful learning. The research further sought to ascertain whether gender and computer experience would have any moderating or mediating effects on the association. The study conceptualized students' MOOC-efficacy in four dimensions (i.e. information searching, making queries, MOOC learning, and MOOC usability), while conceiving meaningful learning as having five dimensions (i.e. cooperative learning, active learning, authentic learning, constructive learning, and intentional learning). Data were collected with a 54-item questionnaire whose reliability indexes ranged from 0.822 to 0.890 for the dimensions. The study's population was identified as university students who have had some experience with MOOCs and who willingly volunteered to participate in the research (N=1,524). A sample of 623 respondents was drawn through simple random sampling. The full-fledged Structural Equation Modeling (SEM) was adopted for data analysis. Key findings include a validated four-dimensional model of students' MOOC-efficacy and a five-dimensional model of meaningful learning. Students' MOOC-efficacy was positively associated with meaningful learning and all of its five dimensions. Gender and computer experience had neither moderating nor mediating effect respectively on the association between students' MOOC-efficacy and meaningful learning. The measurement models of students' MOOC-efficacy and meaningful learning provide further insights into what works in an open online environment. The insights may be used to fulfill learners' needs and preferences. MOOC-efficacy interventions are crucial in order to encourage students' meaningful learning in the e-learning platform.